Efeito do modo ventilatório na cinética do desflurano - Fabri, Daniel Capucci [UNIFESP] (2017)
This study analyzed the pharmacokinetics of desflurane inhalatory anesthetic under pressure controlled ventilation (PCV) and volume controlled ventilation (VCV). The aim of this study was to determine if ventilatory modes (PCV and VCV) interfere with the wash in and wash out of desflurane, since PCV could improve gas exchange, optimizing ventilation perfusion ratio. To achieve this purpose, 33 adults ASA I physical status, were randomly assigned to general anesthesia, with induction of propofol, fentanyl and rocuronium as a neuromuscular blocker. The anesthesia was maintained with a continuous infusion pump of propofol and remifentanil. All patients were ventilated with air and oxygen at 60%, with a flow rate of 6 L/min, in a non-rebreathing system. VCV and PCV were performed with VT of 8 mL/kg, peak inspiratory pressure of 30 cmH2O, inspiratory and expiratory time ratio was 1:2, without PEEP. Respiratory rate was adjusted to maintain EtCO2 between 25 and 40 mmHg. After induction, desflurane at 6% concentration was given for 30 minutes. The patients were ventilated with both PCV and VCV, initiating with one of two modes chosen at random. Desflurane kinetics were determined by recording Fi and FA every 10 seconds in the first minute and at times 5, 10, 15, 20, 25 and 30 minutes. After this period, the vaporizer was turned off and the FA values were recorded at this time and also every 30 seconds on the first 5 minutes. The 33 patients had a mean age of 38.4 ± 6.8 years, mean body weight of 63.3 ± 8.4kg and mean height of 1.60 ± 0.1m. During the induction of anesthesia, uptake and elimination of desflurane did not change the heart rate and mean arterial pressure in both VCV and PCV. During the capture and elimination of desflurane, the VM parameters and BIS readings did not present a statistically significant difference between the two groups. At the elimination of desflurane, there was a statistical difference in the EtCO2 values when the vaporizer was turned off. During wash in of desflurane there was no significant difference in the FA/Fi. During the wash out of this anesthetic, there were statistical differences in two moments, at the first and third minutes. In the conditions of this study, desflurane uptake was similar in both ventilatory modes, however its elimination presented a difference in two moments.